A rapid procedure for the extraction of genomic DNA from intact Aspergillus spores - P C Mol; I MOUYNA; C D'ENFERT (Fungal Genetics Reports, 1998)
Genomic DNA of different species of Aspergillus was prepared from intact spores using the Nucleon MiY kit of Amersham. The method is rapid, does not involve mechanical disruption of the spores nor the use of phenol-chloroform extractions and yields DNA that is suitable for PCR amplification and Southern analysis. The method is also applicable to mycelium ground with glass beads.